Technical note: GAMMORA, a free, open-source, and validated GATE-based model for Monte-Carlo simulations of the Varian TrueBeam. (September 2021) - Leste, Jeremy; Younes, Tony; Chauvin, Maxime; Franceries, Xavier; Delbaere, Alexia; Vieillevigne, Laure; Ferrand, Regis; Bardies, Manuel; Simon, Luc
Highlights: GAMMORA is a tool that creates full Monte-Carlo simulations of the Varian TrueBeam. It generates the files that can be executed with GATE for simple or complex cases. It can be used for research or clinical applications (examples are presented). Particle sources are generated by a pre-trained GAN neural network (gaga). It is as a free and open-source tool validated and used for five years. Abstract: Purpose: Monte Carlo (MC) is the reference computation method for medical physics. In radiotherapy, MC computations are necessary for some issues (such as assessing figures of merit, double checks, and dose conversions). A tool based on GATE is proposed to easily create full MC simulations of the Varian TrueBeam STx. Methods: GAMMORA is a package that contains photon phase spaces as a pre-trained generative adversarial network (GAN) and the TrueBeam's full geometry. It allows users to easily create MC simulations for simple or complex radiotherapy plans such as VMAT. To validate the model, the characteristics of generated photons are first compared to those provided by Varian (IAEA format). Simulated data are also compared to measurements in water and heterogeneous media. Simulations of 8 SBRT plans are compared to measurements (in a phantom). Two examples of applications (a second check and interplay effect assessment) are presented. Results: The simulated photons generated by the GAN have the same characteristics (energy, position, and direction) as the IAEA data. Computed dose distributions of simple cases (in water) and complex plans delivered in a phantom are compared to measurements, and the Gamma index (3%/3mm) was always superior to 98%. The feasibility of both clinical applications is shown. Conclusions: This model is now shared as a free and open-source tool that generates radiotherapy MC simulations. It has been validated and used for five years. Several applications can be envisaged for research and clinical purposes.